Uji Aktivitas Adsoben Karbon Aktif Tempurung Kelapa Termodifikasi dengan Active Site Fe2O3 - Shinta Amelia; Zahrul Mufrodi (Universitas Ahmad Dahlan, 2018)
The use of dyes in the textile industry has a negative impact, namely water pollution if the waste is discharged directly into the river or not treated properly. Liquid waste from the textile industry generally still contains dyes that are harmful to living things and the environment. In this study the dye adsorption method was used by using modified activated carbon from the coconut shell with the addition of the active site Fe2O3. Characterization and activity testing of iron / porous oxide activated carbon adsorbent will be carried out. The type of porous activated carbon used is coconut shell carbon with micropore characters. The stages of this study consisted of the impregnation process of iron oxide on porous carbon, the methylene blue adsorption process and the characterization of the resulting adsorbent. Based on the research that has been done, it can be concluded that the adsorption of Fe2O3 / coconut shell activated carbon is very effectively applied for the absorption of dye wastewater. The adsorption capacity of methylene blue increased with increasing concentrations of loading of active sites of Fe and the percentage of adsorption capacity in the 180 minute reaction was 89.8% with the loading of iron oxide / coconut shell adsorbent 2%. In addition, from the results of the adsorbent activity test with variations in the mass addition of the adsorbent it can be concluded that the mass increase of the adsorbent significantly affected the yield of blue methylene adsorption.